Medial pivot knee in primary total knee arthroplasty - Atzori, Francesco (Ann Transl Med, 2016)
Total knee arthroplasty (TKA) with a medial pivot design was developed in order to mimic normal knee kinematics; the highly congruent medial compartment implant should improve clinical results and decrease contact stresses. Clinical and radiographic mid-term outcomes are satisfactory, but we need other studies to evaluate long-term results and indications for unusual cases.